Prognostic role of positron emission tomography in patients with known or suspected cardiac sarcoidosis. a systematic review and meta-analysis. (25th November 2020) - Bhatia, K; Ramirez, R; Narasimhan, B; Walsh, S; Sud, K; Uberoi, G; Argulian, E
Abstract: Background: Sarcoidosis is a chronic inflammatory disorder of unclear etiology, characterized by the presence of non-caseating granulomas. Cardiac involvement occurs in upto 27 percent of patients, manifesting as atrioventricular blocks, ventricular arrhythmia or sudden cardiac death. Current guidelines cite insufficient evidence for the prognostic utility of positron emission tomography (PET) in patients with cardiac sarcoidosis. Thus, we performed a systematic review and meta-analysis of published studies to ascertain the prognostic significance of PET imaging in patients with suspected or diagnosed cardiac sarcoidosis. Purpose: To review current literature and determine if PET has prognostic utility in patients with known or suspected cardiac sarcoidosis Methods: We performed a comprehensive literature search of electronic databases (Embase, Medline and Web of Science) using MeSH terms and keywords for sarcoidosis and PET from inception through December 2019. Studies were eligible if they included patients with known and/or suspected cardiac sarcoidosis undergoing evaluation by PET with or without perfusion imaging and reported clinical events of interest. An abnormal PET study was defined as the presence of focal or focal-on-diffuse uptake of 18- fluorodeoxyglucose (18-FDG) by visual analysis. In studies with perfusion imaging, patients with only perfusion defects were excluded. The primary outcome of interest was a composite of major adverse cardiac events (MACE), including sustained ventricular tachycardia, sudden cardiac death. Secondary analysis studied association of MACE with focal right ventricular (RV) uptake in patients with an abnormal PET study. Pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using a random-effects model. Heterogeneity of results among the studies was assessed using the Higgins I2 value. Results: Out of a total of 1645 citations, 40 were selected for full-text review. Five studies were included in the final analysis with a total of 465 patients. mean follow-up was 2.3 years. Three of the five studies also reported frequency of abnormal RV uptake of 18-FDG. Patients with abnormal 18-FDG uptake on visual assessment had higher odds of MACE (OR 3.12, CI 1.9–5.01, p<0.00001), compared to known or suspected cardiac sarcoid patients with normal PET studies. Heterogeneity among studies was low (I2 = 0). In patients with an abnormal PET study, abnormal focal RV uptake of 18-FDG was associated with higher odds of MACE (OR 5.24, CI 1.1–25.1, p=0.04), with moderate heterogeneity among studies (I2=41). Conclusion: In patients undergoing PET imaging for known or suspected cardiac sarcoidosis, abnormal metabolism on visual analysis is associated with increased risk of MACE. Furthermore, focal RV uptake further increases the risk of MACE in patients with abnormal PET imaging. Thus, PET imaging can serve as a tool to risk stratify patients with known or suspected cardiac sarcoidosis. Funding Acknowledgement: Type of funding source: None